Expression of Rta in B Lymphocytes during Epstein–Barr Virus Latency. Issue 19 (4th September 2020) - Hwang, Sseu-Pei; Huang, Lin-Chen; Wang, Wen-Hung; Lin, Min-Hsuan; Kuo, Chung-Wen; Huang, Hsiang-Hung; Chang, Li-Kwan
Abstract: Rta of Epstein–Barr virus (EBV) is thought to be expressed only during the lytic cycle to promote the transcription of lytic genes. However, we found that Rta is expressed in EBV-infected B cells during viral latency, at levels detectable by immunoblot analysis. Latent Rta expression cannot be attributed to spontaneous lytic activation, as we observed that more than 90% of Akata, P3HR1, and 721 cells latently infected by EBV express Rta. We further found that Rta is sequestered in the nucleolus during EBV latency through its interaction with MCRS2, a nucleolar protein. When Rta is sequestered in the nucleolus, it no longer activates RNA polymerase II-driven transcription, thus explaining why Rta expression during latency does not transactivate EBV lytic genes. Additional experiments showed that Rta can bind to 18S rRNA and become incorporated into ribosomes, and a transient transfection experiment showed that Rta promotes translation from an mRNA reporter. These findings reveal that Rta has novel functions beyond transcriptional activation during EBV latency and may have interesting implications for the concept of EBV latency. Graphical Abstract: Unlabelled Image Highlights: Rta, considered to be an EBV lytic protein, is also expressed during latency. Rta interacts and colocalizes with MCRS2 in B cells latently infected with EBV. MCRS2 sequesters Rta in the nucleolus to prevent activation of EBV lytic genes. Rta can associate with ribosomes to promote translation.